Pentingnya Pendidikan Karakter pada Anak Sekolah Dasar di Era Digital - Ely Armayani; Fatin Az-Zahra Fatin Az-Zahra; Citra Dewi Utami; Yulia Sri Hikma Hutasuhut; Rachman Rachman; Fauziah Nasution (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
Character education is an effort to implement moral, religious, and ethical values ​​for students through science or knowledge, the application of these values ​​is good for self and others. Children who are in elementary school have developments in their social sphere that are increasing, starting with only socializing with their families at home, then slowly getting to know people around their environment. Children who are at this age are usually able to find out about digital lifestyles, both from the environment where they live and the outside environment. This study intends to see how important character education is for elementary school children in the digital era. Keywords: Education, Character, Digital